USING THE BORDA METHOD ON A DECISION SUPPORT SYSTEM TO CHOOSE THE MOST OUTSTANDING STUDENTS - Saputri, Gustin (Journal of Data Analytics, Information, and Computer Science, 2024)
ABSTRACT Every year, the computer science faculty of Sriwijaya University selects an outstanding student with the goal of rewarding their accomplishments and providing some inspiration. During the selection process, we consider a wide range of student accomplishments and utilize multiple assessment factors to identify exceptional students. Consequently, a Borda method-based decision-making system can be employed to solve the issue. By multiplying the reference value by the ranking's weight, the Borda method is a technique for bolstering collective decisions. The system's outcomes based on preset criteria can provide each student's assessment.. Keyword  :  Borda Method, Decision Support System,  The Outstanding Students